The Use of a Large-strain Drying and Consolidation Model to Optimise Multilift Tailing Deposits - P J. Vardon; Y Yao; L A. van Paassen; A F. van Tol (The Australasian Institute of Mining and Metallurgy, 2015)
Thin-lift atmospheric fine drying (AFD) is a technique used to dewater mine and oil sand tailings, which utilises both self-weight consolidation and atmospheric evaporation. The disposed layers undergo a cyclic drying and rewetting process due to precipitation and deposition of additional lifts on top of the dried layer. The current research aims to optimise the deposition process via use of a numerical model and realistic atmospheric conditions, including both periods of drying and wetting. The model is based upon water balance and includes large strain considerations. A number of material behaviours are characterised using empirical fitting curves based upon laboratory measurement of material characteristics, including both the shrinkage and water retention curves for drying and rewetting. The model is able to model multiple lifts, simulating field scale and realistic climatic conditions within timescales suitable for engineering practice (eg seconds or minutes). The model has been previously validated against controlled laboratory experiments and utilised to simulate field tests. A series of simulations are presented to illustrate the ability of the model to be used as a practical tool for the optimisation of a tailings deposition strategy.CITATION:Vardon, P J, Yao, Y, van Paassen, L A and van Tol, A F, 2015. The use of a large-strain drying and consolidation model to optimise multilift tailing deposits, in Proceedings Tailings and Mine Waste Management for the 21st Century , pp 263–270 (The Australasian Institute of Mining and Metallurgy: Melbourne).